The Analysis of Student's Lack in English Learning of Eleventh Grade Computer Networking Engineering at SMKN 3 Takalar - Pidia Warahma; Subhan Rahmat (Journal of Social Science, 2026)
This study investigates the English language learning difficulties experienced by eleventh-grade students majoring in Computer and Network Engineering at SMKN 3 Takalar, a vocational high school (SMK) in Indonesia. A quantitative research methodology utilizing questionnaires was employed to gather data from 75 students, focusing on their proficiency levels across four key language skills (speaking, reading, listening, and writing), as well as factors contributing to their learning difficulties. The findings revealed that 68% of students experience significant difficulties in learning English, with speaking identified as the most challenging skill (73% of respondents), followed by reading and listening (30.33% each), while writing represents the least difficult area (14% of respondents). The primary factors contributing to these difficulties include insufficient speaking practice (45.3%), limited study time (42.7%), and lack of motivation (38.7%). Additionally, students identified inadequate teaching materials relevant to their technical field (18.7%) and the absence of study partners (30.7%) as significant barriers. However, the study also found that students actively engage in self-directed learning through watching English movies or videos (52%), reading English books or articles (45.3%), and listening to podcasts or music (46.7%) outside the classroom. The majority of students (76%) expressed a strong need for specialized English training focused on technical texts related to computer and network engineering, with 53.3% considering such training very necessary. These findings underscore the critical importance of developing targeted interventions and specialized English for Specific Purposes (ESP) materials tailored to vocational students' unique academic and professional needs. Keywords: English learning difficulties, vocational education, technical English, ESL, qualitative analysis, curriculum development.